2022
DOI: 10.3390/cancers14112740
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Hyperoxia over the Tumor Microenvironment: An Overview Highlighting the Importance of the Immune System

Abstract: Hyperoxia is used in order to counteract hypoxia effects in the TME (tumor microenvironment), which are described to boost the malignant tumor phenotype and poor prognosis. The reduction of tumor hypoxic state through the formation of a non-aberrant vasculature or an increase in the toxicity of the therapeutic agent improves the efficacy of therapies such as chemotherapy. Radiotherapy efficacy has also improved, where apoptotic mechanisms seem to be implicated. Moreover, hyperoxia increases the antitumor immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 114 publications
1
7
0
Order By: Relevance
“…5D ), further confirming the role of hypoxia in RCC tumor cells. An improvement in the immune response related to phagocytosis and leukocyte activation has also been observed, which is consistent with previous findings in many solid tumors (Herrera-Campos et al 2022; Terrén et al 2019). The change in the prominent position from hypoxia- and oxygen-sensing pathways in scRNA-seq to immune response-related pathways in bulk RNA was mainly due to the differences in the analyzed objects.…”
Section: Resultssupporting
confidence: 92%
“…5D ), further confirming the role of hypoxia in RCC tumor cells. An improvement in the immune response related to phagocytosis and leukocyte activation has also been observed, which is consistent with previous findings in many solid tumors (Herrera-Campos et al 2022; Terrén et al 2019). The change in the prominent position from hypoxia- and oxygen-sensing pathways in scRNA-seq to immune response-related pathways in bulk RNA was mainly due to the differences in the analyzed objects.…”
Section: Resultssupporting
confidence: 92%
“…Furthermore, HBO disrupts hypoxia‐mediated immunosuppression and helps PD‐1 Ab trigger robust cytotoxic T lymphocyte responses and durable immune memory to suppress tumor recurrence. 423 , 424 …”
Section: Adjunctive Role Of Hyperoxia In Cancer Therapymentioning
confidence: 99%
“…Furthermore, HBO disrupts hypoxiamediated immunosuppression and helps PD-1 Ab trigger robust cytotoxic T lymphocyte responses and durable immune memory to suppress tumor recurrence. 423,424 Research has shown that an important component of hyperoxia therapy has been overlooked: the immune response. Normally, tumors grow faster than their blood supply, creating a hypoxic environment that stimulates cancer cells to produce a molecule called adenosine, which encourages antitumor T and NK cells to go into a dormant state.…”
Section: Application Of Hyperoxia In Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Genetical changes and uncontrolled cancer growth, which generate intra-tumor hypoxic areas (used by the innovative hypoxia-responsive drug delivery nanoplatforms [78]), cause HIF-1α overexpression enhancing neo-angiogenesis through VEGF synthesis and therefore favoring cancer progression and metastasis [79]. Only recently has the possible role of hyperoxia in tumor necrosis or development started to be investigated [80,81]. For example, leukemia cell lines exposed to a hyperoxic stimulus have been shown to increase the expression of caspase 3, and committing themselves to programmed death and apoptosis preceded morphological modifications of T and B cells [82].…”
Section: Future Perspectivesmentioning
confidence: 99%